Answer:
(a) [tex]v_f=2.414\ m.s^{-1}[/tex]
(b) [tex]v_s=4.828\ m.s^{-1}[/tex]
Explanation:
Let:
mass of father be, [tex]m_f[/tex]
mass of son be, [tex]m_s=\frac{m_f}{2}[/tex]
speed of son be, [tex]v_s[/tex]
initial speed of father be, [tex]v_f[/tex]
After speeding up, speed of father is [tex]v_f+1[/tex]
We know Kinetic Energy is given as
[tex]KE=\frac{1}{2} m.v^2[/tex] .....................................(1)
where:
m = mass
v = velocity
Hence, according to the initial condition the father is having kinetic energy half the kinetic energy of the son.
[tex]KE_s=2.KE_f[/tex]
[tex]\frac{1}{2} m_s.v_s^2=2\times \frac{1}{2} m_f.v_f^2[/tex]
[tex](\frac{m_f}{2})\times v_s^2=2\times m_f\times v_f^2[/tex]
[tex]v_s=2v_f[/tex] .................................................(2)
According to the final condition:
[tex]\frac{1}{2} m_s.v_s^2= \frac{1}{2} m_f.(v_f+1)^2[/tex]
[tex](\frac{m_f}{2})\times v_s^2=m_f.(v_f+1)^2[/tex]
[tex]v_s^2=2(v_f+1)^2[/tex]
[tex]v_s=\sqrt{2}(v_f+1)[/tex].....................................................(3)
(a)
From eq. 2 & 3
[tex]2v_f=\sqrt{2}(v_f+1)[/tex]
[tex]\sqrt{2}\ v_f=(v_f+1)[/tex]
[tex]v_f(\sqrt{2}-1)=1[/tex]
[tex]v_f=\frac{1}{(\sqrt{2}-1)}[/tex]
[tex]v_f=2.414\ m.s^{-1}[/tex]
(b)
putting the above value in eq. (2)
[tex]v_s=4.828\ m.s^{-1}[/tex]